DETERMINAN RETURN SAHAM (PENELITIAN PADA PERUSAHAAN YANG TERMASUK LQ45 YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2016-2018) - Gilman Mughni, - (2021)
This study aims to provide empirical evidence whether there is an effect of solvability, profitability, and stock liquidity simultaneously on stock returns, whether there is an effect of solvability on stock returns, profitability, or whether there is an effect of stock liquidity on stock returns. Included in the LQ45 index for the 2016-2018 period as many as 59 companies while for the sample in this study were 34 companies. The sampling technique in this study was using purposive sampling technique. This study uses multiple linear regression analysis. Data processing in this study using IBM SPSS version 23 software. The results of this study are as follows: Solvability, profitability, stock liquidity have a joint influence on stock returns. Solvability has no effect on stock returns. Profitability has no effect on stock returns. Stock liquidity has a positive effect on stock returns.